Health related quality of life in immigrants and native school aged adolescents in Spain. Issue 8 (13th July 2006) - Pantzer, Karin; Rajmil, Luis; Tebé, Cristian; Codina, Francisco; Serra-Sutton, Vicky; Ferrer, Montse; Ravens-Sieberer, Ulrike; Simeoni, Marie-Claude; Alonso, Jordi
Abstract : Objectives: To compare health related quality of life (HRQL) between native and immigrant adolescents aged 12 to 18 years, and to analyse psychosocial factors associated with HRQL. Design: A cross sectional study of adolescents (12–18 years old) who answered a self administered questionnaire. Setting: All the secondary schools from Lloret de Mar (Girona, Spain). Participants: 1246 participants (88.9% of the eligible students). Main outcome measures: Main outcome was the Spanish version of the Vecu et Sante Percue de l'Adolescent (VSP-A), a HRQL measure addressed to adolescents. Mean scores of the VSP-A index of natives and immigrants were compared, as well as their sociodemographic and health related factors. Multiple regression examined the relation between HRQL and psychosocial factors, controlling for the effect of socioeconomic variables. Results: Half of the sample were boys, in the middle socioeconomic status, and 18.2% were immigrants (n = 226). HRQL score was higher in native Spanish adolescents than immigrants (p<0.01). Multiple regression model explaining 48.1% of the VSP-A variance showed that migration in itself has no statistically significant impact on HRQL, and age, socioeconomic status, social support, discrimination, and psychological distress do play a part. Conclusions: Migrants have worse HRQL than natives but it seems to be mediated by their disadvantage in socioeconomic status, social support, and psychological distress.